Pengaruh Celebrity Endorser, Brand Image dan E-WOM Terhadap Keputusan Pembelian Produk Somethinc Series Serum - Dinda Noer Pratiwi; Ana Noor Andriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine whether there is a significant influence of celebrity endorsers, brand image and electronic word of mouth both simultaneously and partially on purchasing decisions for consumers of Somethinc Series Serum products with research locations in Samarinda, precisely at Mulawarman University. This research was conducted with a quantitative approach through associative methods using a Likert scale. The sampling technique used was a nonprobability sampling technique with a sample of 100 respondents from Mulawarman University students using a questionnaire to be distributed and this study used the Statistical Package for The Social Science (SPSS). This study partially states that the celebrity endorser variable has no significant effect on purchasing decisions for consumers of Something Series Serum products. The brand image variable has a significant effect on consumer purchasing decisions for Somethinc Series Serum products and electronic word of mouth has a significant effect on consumer purchasing decisions for Somethinc Series Serum products among Mulawarman University students. However, simultaneously celebrity endorser, brand image and electronic word of mouth have a significant effect on consumer purchasing decisions for Something Series Serum products. The test results for the coefficient of determination with a value of 0.778, which means that the magnitude of the influence of celebrity endorser, brand image and electronic word of mouth variables on purchasing decisions is 77.8%, while the remaining 22.2% is influenced by other factors not included in the study This